Examples Of Lessons Of Huzur-i Humaayuun In The Ottoman Critical Edition Of Commentary Text With Dissection And Criticizing II - (:unkn) unknown (SAKARYA UNIV, 2015)
The lessons, which have been performed in Ramadan in the presence of the Ottoman sultans on the exegesis of the Quran, called Lessons of Huzur-i Humaayuun. One of the good examples of these lessons was the commentary on the 35th and 36th verses of Sura al-A'raf, which presented by al-Hajj Umar Lutfi Efendi in the presence of the Sultan Abdul-Hamid, the Second, in the month of Ramadan in 1294 AH. After the presentation, thirty-two questions were directed to Umar Lutfi Efendi, and nearly all of these questions were related to the nature of Arabic language.
Keywords: Qur'an; Tafseer; Ottoman; Huzur-i Humaayuun Lesson; Ramadan